Performance evaluation of microwave imaging techniques for enhanced object detection across multiple frequencies and sensors - Mohd Nor Azami, Mohd Adzimnuddin; Abd. Aziz, Mohamad Zoinol Abidin; Ja'afar, Abd Shukur (2024)
Microwave imaging has emerged as a promising technique for object detection and material analysis due to its non-invasive and accurate sensing capabilities. This study focuses on the evaluation of Configuration B, selected for its highest Envelope Correlation Coefficient (ECC), to determine its effectiveness in detecting objects across multiple sensors, frequency ranges, and positions. The experimental results highlight that Frequency 2 delivers the most consistent and reliable detection performance compared to other frequencies, achieving superior results in various configurations. Among the tested sensors, Sensor 4 demonstrates outstanding performance, successfully detecting objects across all frequencies for specific positions, such as Positions 2 and 6. The findings underscore the impact of high ECC and frequency selection in enhancing the accuracy of microwave imaging systems. This study provides a foundation for improving detection capabilities in microwave imaging applications, with potential implications in material analysis and other related fields.